Repeated pregnancy in a bitch, with a diagnosis of extensive cystic endometrial hyperplasia, after the exact determination of the optimal time for breeding - K Jelinkova; E Cigankova; R Vitasek (Veterinární Medicína, 2022)
A 6-year-old bitch was presented to the clinical examination with the aim of determining the optimal time for intrauterine insemination by frozen-thawed semen. The bitch had already had two litters in the past. Extensive cystic endometrial hyperplasia was diagnosed by an ultrasound examination in the bitch. The timing of the endoscopic transcervical insemination by a combination of ultrasonographic examination of the ovaries and determining the progesterone concentrations contributed to the successful conception in the bitch. The ultrasonographic examination of the ovaries represents a non-invasive method which allowed us to view the changes on the ovaries in real time and, thus, is a very suitable method for the specification of the ovulation time in bitches. Cystic endometrial hyperplasia is considered to be a possible cause of infertility. Nevertheless, the bitch repeatedly conceived and had larger litter sizes. Moreover, a considerable reduction in the number of endometrial cysts was observed after the third pregnancy of the bitch. In the described clinical case, the influence of the cystic endometrial hyperplasia on the conception was not demonstrated.